“We need not be ashamed of our own economic profit motive”: Britain, Latin America, and the Alliance for Progress, 1959-63 - Sewell, Bevan (Taylor & Francis (Routledge), 2014)
This article traces British policy discussions over their position in Latin America between 1959 and 1963. In particular, it looks at the way British officials interacted with the John F. Kennedy administration's flagship Alliance for Progress and examines the reasons behind the gradual support for a more engaged UK policy toward the area. This decision, it argues, came about due to a complex set of reasons that challenge the idea that the Anglo-American relationship determined British policy during the cold war. Both the cold war and Anglo-American relations were important in shaping British thinking, but so, too, were calculations over British economic interests. Indeed, as the article demonstrates, it was the interplay of these three elements that shaped British deliberations.